FUN THINKER BOOK UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA SEKOLAH DASAR KELAS I - Dewi, Ni Putu Eva Indra; Kristiantari, Maria Goreti Rini; Werang, Basilius Redan (Pascasarjana Universitas Pendidikan Ganesha, 2024)
This research is motivated by the lack of reading skills among first-grade students in elementary schools, due to a lack of learning media that suit students' characteristics. This study aims to develop the Fun Thinker Book media to improve first-grade students' reading skills. This research is development research using the ADDIE development model. The methods used for data collection are interviews, observations, and questionnaires. The subjects involved in this study include material experts, learning design experts, learning media experts, and first-grade students as product trial subjects. The data analysis techniques used are quantitative descriptive analysis, qualitative descriptive analysis, and inferential statistical analysis. The results of the study indicate that the Fun Thinker Book media design, in the form of a colored picture book and display frame, was developed to increase students' interest in learning and to use the ADDIE development model. Second, the feasibility of the media was assessed through expert reviews of learning content (96.88%), learning design (93.75%), learning media (95%), individual trials (95.84%), and small group trials (94.1%). Third, the effectiveness of the Fun Thinker book, based on the t-test calculation, produces a t value of 11.708 and a ttable value of 1.714. When compared, the tvalue is greater than the ttable value, so H0 is rejected and H1 is accepted. Thus, this study shows that the Fun Thinker book media is effective for first-grade elementary school students, resulting in a 5% increase in reading ability.